Incidence and antimicrobial susceptibility of Salmonella, Listeria, and Campylobacter spp. in raw “souvlaki” marketed in Thessaloniki (Northern Greece) - SOULTOS (Ν. ΣΟΥΛΤΟΣ) N.; IOSSIFIDOU (Ε. ΙΩΣΗΦΙΔΟΥ) E.; PSOMAS (Ε. ΨΩΜΑΣ) E.; TZIKAS (Ζ. ΤΖΗΚΑΣ) Z.; LAZOU (Θ. ΛΑΖΟΥ) T. (Journal of the Hellenic Veterinary Medical Society, 2018)
Souvlaki is a popular Greek meat product consisting of small chunks or cubes of pork threaded on a small wooden or metal skewer. In the present study, 105 samples of raw pork souvlaki obtained from retail shops in Thessaloniki (Northern Greece) were screened for the incidence of Salmonella, Listeria, and Campylobacter and their susceptibility to various antimicrobial agents; serotyping of the isolates was also performed. Of the samples tested, 1.9% were positive for Salmonella and yielded 3 serovars (S. SaintPaul, S. Fyris and S. Typhimurium); 31.4% proved positive for Listeria spp. with 6.7% yielding L. monocytogenes isolates belonged to molecular serogroups 2 (serotypes 1/2c and 3c) and 4 ( serotypes 4b, 4d, and 4e). Campylobacter spp. were not detected in any of the samples tested. The antimicrobial susceptibility to various antimicrobial agents of 11 Salmonella strains and 7 L. monocytogenes strains was also determined by disc diffusion method. Salmonella spp. were susceptible to a panel of 12 antibiotics but displayed intermediate resistance to tetracycline. L. monocytogenes isolates were resistant to nalidixic acid and ceftriaxone, partly resistant to clindamycin and cefotaxime, but sensitive to all antibiotics commonly used in veterinary and human listeriosis. Our findings indicate that souvlaki could be a potential vehicle of food borne infections due to strains of L. monocytogenes and Salmonella spp. in the case of inadequate thermal processing. In addition, good hygienic practices must be applied to avoid cross-contamination during preparation or handling of the product.